Reimagining Christian Doctrine? A Critical Analysis of Anthony Thiselton's Hermeneutics of Doctrine - Panda, Baptista Alberto (Stellenbosch : Stellenbosch University, 2026)
Thesis (MTh)--Stellenbosch University, 2026.